Annual and seasonal grid-point cloud cover anomaly series over Italy (1951-2018) - Veronica Manara; Michele Brunetti; Martin Wild; Maurizio Maugeri (PANGAEA, 2023)
These datasets contain annual and seasonal anomaly series of total cloud cover over Italy. The anomaly series are expressed as additive anomalies with respect to the period 1961-1990. The series are gridded series with a resolution of 1° exttimes 1°. They are obtained interpolating by means of an Inverse Distance Weighting approach a quality-checked and homogenized dataset of human observations of total cloud cover series over the 1951-2018 period and referred to 12 UTC.